Struggles for the Character of the Roman Catholic Church in Czechoslovakia, 1948-1989 - Tížik, Miroslav (Eurostudia)

(untitled) (Le Centre canadien d’études allemandes et européennes, 2015)
After the Communist Party of Czechoslovakia came to power in 1948, power struggles followed between political parties and long-running internal struggles within the country’s Roman Catholic Church over the church’s character and organizational structure. These struggles related not only to purely theological issues, but also to the ideals of communism (and, later, socialism), the Communist Party and its program. The internal plurality within the church throughout the whole period of the people’s democracy and state socialism in Czechoslovakia calls into question the dualistic image of struggles between the church and the Communist Party, and it complicates the image of the church as a victim of the Communist regime. In particular, the crucial periods from 1948 to 1952 and from 1968 to 1969 suggest that, throughout much of the communist period there persisted tensions between the higher and lower clergy and there were diverging views on how the church should function; these tensions took on a diversity of shapes and varied in intensity.